Effectiveness of pegfilgrastim prophylaxis in preventing febrile neutropenia during R-FC chemoimmunotherapy for chronic lymphocytic leukemia: A multicenter prospective phase II study - Jeon, Youngwoo; Yang, Duk-Hwan; Oh, Suk-Joong; Park, Jin-Hee; Kim, Jung-Ah; Kim, Sung-Young; Choi, Chul-Won; Lee, Won-Sik; Kim, In-Ho; Mun, Yeung-Chul; Min, Gi June; Eom, Ki-Seong; et al. (Frontiers in Oncology, 2023)
Background: A chemotherapy of rituximab, fludarabine and cyclophosphamide (R-FC) has been accepted as a promising frontline chemotherapy in selected patients with chronic lymphocytic leukemia (CLL). Although R-FC regimen is a relatively dose-dense regimen and neutropenia incidence is more than 50%, primary prophylactic pegfilgrastim was not fully recommended in the clinical field. Therefore, the study evaluated the prophylactic effectiveness of pegfilgrastim to reduce the incidence of febrile neutropenia associated with R-FC of patients with CLL. Patients and methods: A single-arm, multicenter, prospective phase II study was designed to assess the efficacy of prophylactic pegfilgrastim. Thirty-four CLL patients were enrolled and analyzed for neutropenia and other related factors, and comparative analysis was performed with historical cohort. Results: Compared with our historical cohort, incidence of grade 3-4 neutropenia and febrile neutropenia was remarkably reduced during any cycle of chemotherapy (14.7% vs. 48.2% of study cohort vs. historical cohort during C1, 5.9% vs. 65.8% during C2, 12.9% vs. 80.6% during C3, 10% vs. 84.6% during C4, 3.4% vs. 83.6% during C5, and 10.7% vs. 85.7% during C6, p <0.001). Also, cumulative incidence of disrupted chemotherapy was noticeably reduced in study cohort on any cycles of R-FC regimen (8.8% vs. 22.2% of study cohort vs. historical cohort on C2, 9.7% vs. 25.2% on C3, 13.4% vs. 26.9% on C4, 13.8% vs. 45.2% on C5, 17.9% vs. 47.3% on C6, p=0.007). In addition, treatment-related mortality was 5.9%, which significantly reduced compared to 9.6% of our historical cohort (HR 0.64, 95% CI 0.42–0.79, P = 0.032). Conclusion: Primary prophylactic pegfilgrastim is effective in the prevention of neutropenia/ febrile neutropenia, and infection-related mortality during R-FC regimen in patients with CLL.